Clinical Correlation of Intraoperative Neuromonitoring in 319 Individuals Undergoing Posterior Decompression and Fixation of Spine. Issue 3 (April 2021) - Modi, Hitesh N.; Goel, Shakti A.; Desai, Yatin J.; Modi, Poonam N.
Abstract : Study Design: This was a prospective study. Objectives: To correlate improvement in motor evoked potential (MEP) during spine surgery with postoperative clinical improvement. Materials and Methods: Three hundred fifty-three patients operated for posterior spinal decompression and fixation surgeries were prospectively selected and followed up. Patients who underwent lumbar, dorsal, and cervical surgeries were grouped into—group A, B, and C, respectively. Intraoperative neuromonitoring was done using MEP with free-running electromyography. Improvements in MEP scores were calculated in percentage. Similarly, postoperative improvement in Oswestry disability index (ODI) and visual analog scale (VAS) scores at 3 months were calculated in percentage. Improvements in MEP scores were correlated with clinical improvement using the Spearman ρ test and the r value was calculated to find out the association. Results: Of 353 patients, 319 (250—group A, 38—group B, and 31—group C) were included for the study. VAS and ODI improved significantly from preoperative 8.5±0.8 and 62.9±14.5, to postoperative 2.3±1.1 and 15.9±11.5, respectively, in the entire group. Average preoperative MEP were 127.8±191.0 mV on the right side and 132.3±206.6 mV on the left side, which significantly improved to 163.7±231.2 mV ( P =0.0001) and 155.2±219.6 mV ( P =0.0001), respectively, showing 157.0% and 178.5% improvement. Correlating MEP improvement with postoperative improvement in ODI showed poor correlation ( r =0.088 right and 0.030 left sides). Similarly, correlating MEP improvement with improvement in VAS showed r =0.110 on the right and −0.023 on the left side suggesting poor correlation. Postoperative neurological complications (0.56%) were found in 2 patients in the form of screw malpositioning. Conclusions: Intraoperative neuromonitoring showed significant improvement during posterior decompression and fixation surgery, and reduction in postoperative neurological complication. The study also exhibited significant postoperative clinical improvement. However, improvement in MEP did not correlate with postoperative clinical improvement suggesting that it has no predictive role.